CFD Simulation of Catalytic Combustion of Benzene (Iranian Journal of Chemical Engineering)
This paper reports the result of CFD simulation of catalytic oxidation of benzene on monolithic catalyst. The geometries ofthe catalyst and reactor were designed in Gambit software and simulation of catalytic oxidation was carried out in fluent 6.2. Results of simulation showed excellent agreement with the experimental data. This study confirmed the accuracy of the used model in this simulation (Mars van Krevelen). Furthermore, CFD made it possible to obtain a more accurate view ofheat transfer and fluid flow. This study confirmed CFD is the best tool for study offluid regime and heat transfer and especially, concentration of species, and surface deposition along the reactor in the chemical process.